(untitled) (Global Journal of Science Frontier Research, 2023)
This study was conducted during the two successive seasons 2021 and 2022 using "Anna" apples. The trees were sprayed by using some organic calcium solution to compare their efficacy on providing the skin and flesh tissues with calcium which reflects on the fruit quality. The trees were sprayed twice at the rapid elongation and maturity stages in both seasons treatments included tap water as the control, calcium lignosulfonate (at 0.2%) and (at 0.4%), calcium foliate (at 0.2%) and (at 0.4%), calcium acetate (at 1%), calcium acetate (at 1%) plus urea (at 1%) and calcium acetate (at 1%) plus ethanol (at 2%). The non-ionic surfactant top film at 0.05% (v/v) was added to all treatments to reduce the surface tension and to increase the contact angle. Treatments resulted in increasing calcium content in the skin and the flesh of "Anna" apples the highest magnitude of increase was obtained in the skins and flesh of calcium acetate treated fruits plus ethanol as well as in the flesh.